Ecology and distribution of the Amur Chebachok Pseudorasbora parva (Temminck et Schlegel, 1846) as a biologically invasive species in the delta and estuarine coast of the river Don - A. V. Starsev; A. A. Korchunov; N. I. Rabazanov; R. N. Rabazanov (Юг России: экология, развитие)
Aim. To analyze the results of ichthyological monitoring in order to identify the role  of an invasive fish species, Pseudorasbora parva – known in Russia as the Amur Chebachok – in the ichthyological community of the River Don estuary littoral and delta.   Material and Methods. Research work was carried out in the prodelta and estuarine  watercourses of the Don delta in the period 2007‐2017. To catch the fish, we used  bimtral, drag nets, gill nets and other fishing gear. Standard methods were applied to  process ichthyological material. A total of 902 specimens of the Amur chebachok  were examined.   Results. The general characteristics of the invasive species from watercourses of the  delta and from Taganrog Bay are given. Its role in the formation of ichthyofauna and  its relationship with native species in new habitats has been determined. Dimensionmass indicators and other biological parameters of the species are given.  Conclusion. The linear structure of the local population of the Amur chebachok consists of different size groupings corresponding to certain ages. The process of acclimatization of the Amur chebachok in the Don delta is associated with certain interactions with elements of the local biocenosis. It was proved that when there is a high  number, both in pond farms and in natural water bodies, the species is an acute food  competitor to juveniles of both farmed or local fish. Its rapid spread is due to the  high survival rate of offspring, high environmental plasticity, rapid growth, short  puberty and the migratory activity of larvae and fry.